(untitled) (Sociologisk Forskning, 1996)
This article is a shortened version of presentation made at the Second Annual Theory, Culture and Society Conference in Berlin, August 1995 and will appear in its entirety in a forthcoming volume of proceedings. Tracing the history of the song ”We Shall Overcome” from its origins in the experiences of African American slaves to its current status as social movement song par excellence is offered as an illustration of what the paper identifies as the cultural praxis of social movements. The recent cultural turn in social movement research is pushed further and deeper as it is suggested that current research has neglected the historical dimension. Tradition and ritual, it is suggested, which link current mobilizations to the past and a collective memory, should be analyzed as central elements in the making of social movements.